A Botswana Rural Women’s Transition to Urban Small Business Success: Collective Struggles, Collective Learning - Gabo Peggy Ntseane (Adult Education Research Conference, 2000)
Although (75%) of women who move from rural areas to urban areas engage in small businesses, most of these small businesses never grow due to problems related to patriarchal structures. Context, non-competitive networking, and experiential learning are necessary to negotiate patriarchy for Botswana women’s business success.